IMPROVING THE METHODOLOGY OF USING MOBILE GAMES TO IMPROVE THE TRAINING EFFICIENCY OF YOUNG VOLLEYBALL PLAYERS - Qazokov Sodiq Ramazonovich (TADQIQOTLAR, 2025)
Abstract: a comprehensive review of the methodology of using motion studies to  improve  the  training  of  young  volleyball  player.  After  tea  To  the  physical development  of  volleyball  in  the  spirit  of  making  a  team  and  product,  shorts recommending games and fast action team. By the individuality of each athlete after your pay grade to learning and new learning techniques for coaches, and sharing your experiences, were reported in the potential of young athletes can be enhanced. The highway encourage proposals from the volleyball player to be active and successful.